EFEKTIVITAS PERATURAN PEMERINTAH NO.48 TAHUN 2014 DALAM PENGELOLAAN BIAYA PENCATATAN NIKAH (STUDI KASUS PADA KUA KEC.TALUN KABUPATEN CIREBON) - Ali Wahyuddin (UIN Siber Syekh Nurjati Cirebon, 2019)
ABSTRACT The rise of legal events that befell the officers entangled in gratuities and extortion due to the old marriage cost mechanism is no longer in accordance with the tool of Non-Tax State Revenue and has not adopted the development of the times so that new patterns need to be formulated in the hope that the welfare of implementing apparatus will be accompanied by improved public services and image improvement The Office of Religious Affairs in the eyes of the community so that a new mechanism that is more equitable for the city and the implementing apparatus for registering marriages is needed, and that hope is realized by the issuance of PP No. 48 of 2014 concerning Marriage Costs.Keywords: Regulations; Costs; Marriage; PP No. 48 of 2014 ABSTRAKMaraknya peristiwa hukum yang menimpa penghulu terjerat gratifikasi dan pungli dikarenakan mekanisme biaya nikah lama sudah tidak lagi sesuai dengan mekanisme Penerimaan Negara Bukan Pajak serta kurang mengadopsi perkembangan zaman sehingga perlu dirumuskan pola baru dengan harapan meningkatnya kesejahteraan aparatur pelaksana dibarengi dengan peningkatan pelayanan terhadap masyarakat dan perbaikan citra Kantor Urusan Agama di mata masyarakat sehingga perlu dirumuskan mekanisme baru yang lebih berkeadilan bagi masyarakat dan aparatur pelaksana pencatatan perkawinan dan harapan itu terwujud dengan terbitnya PP No. 48 Tahun 2014 tentang Biaya Nikah.Kata Kunci: Peraturan; Biaya; Nikah; PP No 48 Tahun 2014